Peningkatan Kompetensi Guru Membangun Budaya Literasi Melalui Pembinaan Profesional Dengan Pendekatan Kooperatif Di SMKN 1 Almubarkeya Ingin Jaya - Fuadi, Sukmanil (Asas Wa Tandhim: Jurnal Hukum, Pendidikan Dan Sosial Keagamaan, 2023)
Research on improving teacher competence in building a literacy culture through professional development activities with a cooperative approach. This type of research is action research (action research). The research subjects were 5 teachers. Data collection techniques are carried out by observation and documentation activities. Data validation uses triangulation techniques. Data analysis used descriptive techniques. The results showed an increase in the teacher's ability to build a literacy culture from an average score of 50.17 with a low score criterion, to 69.92 moderate score criteria and to 87.83 very good score criteria in the last cycle. Explanation of completeness individually in the initial conditions that there were no teachers who were declared complete, becoming 8 teachers (53.33%), and 15 teachers (100%) in the second cycle.